Yukoners dining at the Regina Café, Dawson, Yukon Territory, approximately 1899. - Hegg, Eric A., 1867-1948 (Hegg & Company, 1899)
Shows men dressed in formal attire, Captain Jack Crawford in seated in center. Caption on image: "Yukoners dining at the Regina Cafe."